ANALISIS BIAYA PENGOBATAN PENYAKIT JANTUNG KORONER PADA PASIEN RAWAT INAP DI RUMAH SAKIT X - Syafika Alaydrus (Medical Sains : Jurnal Ilmiah Kefarmasian, 2020)
Coronary heart disease (CHD) is one of the most common types of heart disease. The number of sufferers causes the amount of costs incurred. The purpose of this study is to see the effectiveness of CHD costs based on INA-CBGs financing. The analysis used was descriptive analysis, ANOVA test One sample t analysis. test and correlation test, the respondents used were CHD patients in the UNDATA PALU Hospital as many as 56 people. The sample uses purposive sampling. Data collection uses observation through medical records. Based on the results of the study for the average real cost of using Mandiri BPJS of Rp. 2,681,681.0. For payments using PBI BPJS of Rp. 2.791,870.2. For payments using PNS BPJS of Rp. 2,778,843.0. Where as the payment uses the PENSION PENSION PNS for Rp. 2,933,510.8.Â Kata kunci : Penyakit Jantung Koroner (PJK), Pembiayaan INA-CBGsÂ